AWARENESS OF BRAIN DEATH DOCUMENTATION AMONG POST GRADUATE TRAINEES IN LAHORE - RANA, MA; AWAD, AHA; QAYYUM, MA; BHATTI, MA; KHALID, MS; ZARTASH, S; ZAHOOR, M; PERVAIZ, R; HAFEEZ, MM (Biological and Clinical Sciences Research Journal, 2022)
Brain death is the complete and irreversible cessation of all activity in the brain, including the brain stem and cortex. It's critical to declare someone brain dead to stop providing life support or donating their organs. This study was carried out to evaluate postgraduate trainee doctors’knowledge and understanding of brain death in the Lahore cityas the Punjab Human Organ Transplant Authority (PHOTA) moves towards cadaveric donor program. Utilizing the universal sample approach, a questionnaire-based survey with 150 senior trainee registrars from several postgraduate fields was conducted at four teaching hospitals in Lahore. The registrars had 45 minutes to finish a pre-validated questionnaire form that inquired about their perspectives, knowledge, and the procedure for determining brain death. Quantitative data were shown as means, whereas qualitative data was shown as frequencies. SPSS software version 21 was used for statistical analysis. The questionnaire was given to 150 postgraduate trainees in total, of which 70% were men and 30% were women. Approximately 88.90% of participants were able to define brain death as the total cessation of all brain functioning, including brainstem reflexes. 121 doctors (82%) said yes when asked if they would perform brainstem reflexes twice, six hours apart. Only 40(26.66%) doctors were able to reliably identify the absence of brain stem responses, such as the corneal and pupillary reflexes. Just 10 (6.66%) out of 150 participants were able to correctly define what a positive apnea test means, but 33.33% of respondents agreed that it is a necessary test to demonstrate the cessation of brain stem activity. 15.50% of resident doctors had knowledge that a committee of four doctors was required to declare brain deathThe gold standard test for determining brain death, according to 4.66% of responders, is cerebral angiography. 95% of respondents were ignorant of the measures being taken by the Punjab Human Organ Authority (PHOTA) concerning the dead organ harvesting program or that such a program even existed. Although everyone agreed that getting an agreement before organ harvesting was required but only five trainees understood the exactmethodologyof taking consent and how it functioned. The PGRs lacked knowledge about brain death, its detection and documentation, concerning cadaveric donor organ donation and transplantation. The results of this study showed a lot of work needed to start cadaveric organ transplant safely.